Comparison of different dosing strategies of intratracheally instilled budesonide on meconium injured piglet lungs. Issue 7 (July 2017) - Lin, Chih‐Hsueh; Jeng, Mei‐Jy; Yang, Yi‐Chiang; Hsiao, Yu‐Hsuan; Kou, Yu Ru
Abstract: Background: Severe inflammation plays a vital role in the pathogenesis of meconium aspiration syndrome (MAS). Intratracheal (IT) instillation of corticosteroids may be beneficial for MAS in optimizing local effect and reducing systemic adverse effects, but the optimum dosing course remains open to question. Methods: Thirty meconium‐injured newborn piglets were enrolled into six study groups. The first four groups consisted of the IT instillation of 0.25/0.5 mg/kg using either one (IT‐B251/IT‐B501) or two (IT‐B252/IT‐B502) doses of budesonide, while the other two groups were the intravenous (IV) dexamethasone (0.5 mg/kg) (IV‐Dex) group and the control group (Ctrl). Vital signs and cardiopulmonary functions were monitored throughout the experiments. Pulmonary histology was examined after completing the experiments. Results: Both the IV‐Dex and IT‐B501 groups got significant improvement in oxygenation ( P < 0.05). Lung compliance became worse after one dose of 0.25 mg/kg of IT budesonide. Pulmonary histology revealed that there were significantly lower lung injury scores for all treatment groups compared to control group, especially at the non‐dependent sites of both the IT‐B501 and IT‐B502 groups. There was no significant difference between double‐ and single‐dose groups, no matter whether 0.25 or 0.5 mg/kg of budesonide was used. Conclusions: IT instillation of one dose of 0.5 mg/kg budesonide is beneficial in treating meconium‐injured piglet lungs during the first 8 h of injury, but a second dose at an interval of 4 h does not have a superior beneficial effect compared to one dose.